Chemical Composition and Antioxidant Activity of Essential Oil of Bamboo Leaves from Four Species in China - Hu, Chong-Jiu; Liao, Hai-Bing; Yuan, Ke; Hu, Jia-Hui; Lin, Xin-Chun (Asian Journal of Chemistry, 2011)
The chemical compositions of essential oil from Pseudosasa amabilis (McClure)Keng f., Pleioblastus gramineus (Bean) Nakai, Phyllostachys vivax f. aureocaulis N. X. Ma. and Indocalamus latifolius (Keng) McClure obtained by steam distillation were analyzed by gas chromatography and gas mass spectrometry. The relative content of the constituents from the essential oil were determined by area normalization method, then compared and analyzed the experimental result. Sixty eight constituents were separated and identified by GC/MS from four species of bamboo leaves. Nineteen kinds of compounds which all contained in the four species of bamboo leaves and 16 kinds of compounds which all contained in the three bamboo leaves were found. Meanwhile, the effect of scavenging free radicals of essential oil was studied by using the DPPH assays with Trolox as control to evaluate their antioxidant capacities. The essential oil of bamboo leaves from four species all possesses certain antioxidant capacity and showed a positive correlation with the essential oil's concentration. The results provide evidence for studying essential compositions from different species of bamboo leaves for further development.